Experimental study of a breastshot waterwheel with the degree of inclination of the nozzle spray against the tip speed ratio - Muhammad Helmi Kurniawan; Khusnul Khotimah Ayuningtiyas; Ridho Dwi Syahrial (International Journal of Basic and Applied Science, 2023)
The energy crisis is a severe problem facing the world, including Indonesia. Along with the times, innovation is needed to implement sustainable energy. Non-fossil energy sources have not been widely used, and efforts are still needed to utilize these energy sources. The waterwheel was the first device used in water production. One of the innovations for the sustainability of non-fossil energy is to make a waterwheel. There are still several waterwheels in Indonesia, but an investigation is needed to determine their condition. So in this study, investigating the breastshot water wheel uses a nozzle-based construction with variations in the degree of inclination of the spray against the TSR value. The results showed that the greater the inclination of the nozzle angle, the higher the velocity of the water flow when it enters the wheel. Adding water speed to this wheel will increase the momentum and tangential force. An increase in the tangential force will increase the wheel's torque so that the wheel strength will increase. This increase in power will, of course, result in greater efficiency, thereby increasing the tip speed ratio (TSR).